(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Stature is one of the important criteria for establishing identification of unknown person/dead body. Reconstruction of stature is a tedious job when dead bodies are mutilated, burnt or skeletonised. In this study, attempt is made to reconstruct stature by percutaneous measurement of hand as in cases of dismembered remains where most of other body parts are damaged. Stature is calculated from the length of hand which is the distance from the mid-point of styloid process of radius and ulna on the back of wrist to tip of middle finger. Standing height and length of hand are measured in 100 adult male and female students of 19–25 years of age and regression equation is derived by using formula. ݕ = ߨݕߜݔߜ̅.ݕ − (̅ݔ − ݔ) Here x stands for length of hand and y the standing height. Regression equations are derived separately for both the sexes which is 5.1x + 67.9 for male and 4.8x + 70.2 for female. The multiplication factor for hand is 8.5 & 8.7 for male and female, respectively. Stature calculated by regression equations is found close to the actual height (±3 cm) and by multiplication factors, it is more than ±5 cm in large number of the cases. This indicates regression equations are superior and more reliable than multiplication factors.